SOURCE RUPTURE PROCESS OF THE OCTOBER 25TH, 2010 MENTAWAI EARTHQUAKE INFERRED FROM INVERSION OF REGIONAL SEISMIC DATA USING EMPIRICAL GREEN'S FUNCTION - (NIM : 22412310); Pembimbing : Afnimar, Ph.D, PRIYOBUDI
Rupture processes of the October 25th, 2010 Mentawai earthquake inferred from inversion of regional seismic data using Empirical Green's function (EGF). An aftershock of Mw 5.4 was used as Green's function to construct seismogram of target event which had Mw7.8. The seismograms from five regional seismic stations of The Meteorological, Climatological and Geophysical Agency (MCGA) of Indonesia were used in this analysis. The displacement seismograms of P phase were inverted to estimate moment release, rupture duration, and slip distribution. The result is a more detailed image of slip distribution than previous study, especially near the hypocenter. One asperity obtained from previous study, in this study it is divided into two large asperities, with maximum slip of 5 m and 8.7 m. The other difference was the momen rate function that indicated two different rupture characteristics occurred during the whole rupture processes. In the first 25 sec of them has a typical earthquake character, while between 25-105 sec of them has slow earthquake one (tsunami earthquake). Those detailed features can be obtained due to the use of higher frequency content of regional seismic data. Heterogeneity of slip distribution and two difference rupture characters indicated rigidity variation that caused by complex geological features of the fault interface. These complex features can be interpreted as horsts and grabens structure. This interpretation is supported by a seismic section along southern part of rupture area. The variation of slip was controlled by sediment thickness and their mechanical properties.